Israeli identity between Orient and Occident - Tal, David (Routledge studies in Middle Eastern society, 2013)
"For many years before and after the establishment of the state of Israel, the belief that Israel is a Western state remained unchallenged. This belief was founded on the predominantly western composition of the pre-statehood Jewish community known as the Yishuv. The relatively homogenous membership of Israeli/Jewish society as it then existed was soon altered with the arrival of hundreds of thousands of Jewish immigrants from Middle Eastern countries during the early years of statehood. Seeking to retain the western character of the Jewish state, the Israeli government initiated a massive acculturation project aimed at westernizing the newcomers. More recently scholars and intellectuals began to question the validity and logic of that campaign. With the emergence of new forms of identity, or identities, two central questions emerged; to what extent can we accept the ways in which people define themselves? And on a more fundamental level; what weight should we give to the ways in which people define themselves? This book suggests ways of tackling these questions and provides varying perspectives on identity, put forward by scholars interested in the changing nature of Israeli identity. Their observations and conclusions are not exclusive, but inclusive, suggesting that there cannot be one single Israeli identity, but several. Tackling the issue of identity, this multidisciplinary approach is an important contribution to existing literature and will be invaluable for scholars and students interested in Cultural Studies, Israel, and the wider Middle East"